Novel oxazolidinone calcitonin gene-related peptide (CGRP) receptor antagonists for the acute treatment of migraine. Issue 21 (1st November 2015) - Crowley, Brendan M.; Stump, Craig A.; Nguyen, Diem N.; Potteiger, Craig M.; McWherter, Melody A.; Paone, Daniel V.; Quigley, Amy G.; Bruno, Joseph G.; Cui, Dan; Culberson, J. Christopher; Danziger, Andrew; Fandozzi, Christine; et al.
Graphical abstract: Abstract: In our efforts to develop CGRP receptor antagonists as backups to MK-3207, 2, we employed a scaffold hopping approach to identify a series of novel oxazolidinone-based compounds. The development of a structurally diverse, potent (20, cAMP + HS IC50  = 0.67 nM), and selective compound (hERG IC50  = 19 μM) with favorable rodent pharmacokinetics ( F  = 100%, t 1/2  = 7 h) is described. Key to this development was identification of a 3-substituted spirotetrahydropyran ring that afforded a substantial gain in potency (10 to 35-fold).